2010
DOI: 10.1007/s11845-010-0601-4
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of hypopharyngeal packing in nasal surgery: a pilot study

Abstract: Based on our findings, the authors recommend against placing hypopharyngeal packs for the purpose of preventing postoperative nausea and vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 9 publications
1
42
1
1
Order By: Relevance
“…The main premise for the use of pharyngeal packs in sinus surgery theoretically is to prevent ingestion of blood products to reduce postoperative nausea and vomiting. Our study found that the placement of a pharyngeal pack did not reduce PONV, as has been found in the literature . Our findings suggest that there is no need to place a pharyngeal pack to prevent nausea/vomiting in patients undergoing endoscopic sinus surgery.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The main premise for the use of pharyngeal packs in sinus surgery theoretically is to prevent ingestion of blood products to reduce postoperative nausea and vomiting. Our study found that the placement of a pharyngeal pack did not reduce PONV, as has been found in the literature . Our findings suggest that there is no need to place a pharyngeal pack to prevent nausea/vomiting in patients undergoing endoscopic sinus surgery.…”
Section: Discussionsupporting
confidence: 80%
“…The literature is at times conflicting and inconclusive on whether pharyngeal packs have an effect on postoperative pain and PONV. Previous studies have found that pharyngeal packs are associated with increased postoperative pain, whereas other studies reported no difference in pain postoperatively . The most recent randomized controlled trials in the Unites States by Korkut and Fennessey reported no difference in pain postoperatively with or without the placement of a throat pack.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations